2020
DOI: 10.1523/jneurosci.0902-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Modulate Activity-Dependent AMPA Receptor Transport in C. elegans

Abstract: The AMPA subtype of synaptic glutamate receptors (AMPARs) plays an essential role in cognition. Their function, numbers, and change at synapses during synaptic plasticity are tightly regulated by neuronal activity. Although we know that long-distance transport of AMPARs is essential for this regulation, we do not understand the associated regulatory mechanisms of it. Neuronal transmission is a metabolically demanding process in which ATP consumption and production are tightly coupled and regulated. Aerobic ATP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 110 publications
(160 reference statements)
4
17
0
Order By: Relevance
“…In addition, the application of DPCPX, DCKA and AP5 have been previously reported to reverse the protective effects of MnTMPyP on synaptic transmission post-ischemia [ 20 ]. It has been reported that superoxide is produced by NMDA receptors in an attempt to achieve a state of NMDA receptor hypofunction in order to limit damaging Ca 2+ influx [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the application of DPCPX, DCKA and AP5 have been previously reported to reverse the protective effects of MnTMPyP on synaptic transmission post-ischemia [ 20 ]. It has been reported that superoxide is produced by NMDA receptors in an attempt to achieve a state of NMDA receptor hypofunction in order to limit damaging Ca 2+ influx [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in C . elegans showed that H 2 O 2 blocks inactivating currents in ASER [ 81 ] and that pretreatment with H 2 O 2 blocked subsequent excitation of ASH sensory neurons by specific inputs [ 82 , 83 ] and lowered the spontaneous activity of AVA interneurons [ 84 ]. The H 2 O 2 concentration that we used in our studies is within the range produced by bacterial pathogens [ 19 21 ] and detected in inflammation or reperfusion after ischemia in mammals [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…We note that H 2 O 2 prevented the responses to E. coli of a wide variety of sensory neurons. Previous studies in C. elegans showed that H 2 O 2 blocks inactivating currents in ASER (Cai and Sesti, 2009) and that pretreatment with H 2 O 2 blocked subsequent excitation of ASH sensory neurons by specific inputs (Li et al, 2016; Zhang et al, 2020) and lowered the spontaneous activity of AVA interneurons (Doser et al, 2020). The H 2 O 2 concentration that we used in our studies is within the range produced by bacterial pathogens (Bolm et al, 2004; Jansen et al, 2002; Moy et al, 2004) and detected in inflammation or reperfusion after ischemia in mammals (Schroder and Eaton, 2008; Sprong et al, 1997).…”
Section: Discussionmentioning
confidence: 99%